2023
DOI: 10.3390/vaccines11121804
|View full text |Cite
|
Sign up to set email alerts
|

Parental Vaccine Literacy: Attitudes towards the COVID-19 Vaccines and Intention to Vaccinate Their Children Aged 5–11 Years against COVID-19 in Thailand

Wantana Maneesriwongul,
Suhong Deesamer,
Nipaporn Butsing

Abstract: Background: High rates of population immunity are needed to control the COVID-19 pandemic. This study aimed to assess parents’ intention to have their children, aged 5–11 years, vaccinated against COVID-19 and its influencing factors in Thailand. Methods: A cross-sectional online survey was conducted before the nationwide COVID-19 vaccine rollout for children aged 5–11 years in Thailand. A sample of 542 parents with children in this age group was recruited online. Results: In total, 58.8% of parents intended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These variables include communication, knowledge, beliefs, attitudes, behaviors, self-efficacy, and competencies (Figure 2). As mentioned, nine studies included in the updated review support the notion of a direct negative association between VL and VH [26,27,30,32,34,35,[38][39][40], while the other three showed a partial or complete mediating effect [8,33,37]. These findings were contradicted by other investigations published during the same period [28,31].…”
Section: Step 3: Theoretical Frameworkmentioning
confidence: 84%
See 1 more Smart Citation
“…These variables include communication, knowledge, beliefs, attitudes, behaviors, self-efficacy, and competencies (Figure 2). As mentioned, nine studies included in the updated review support the notion of a direct negative association between VL and VH [26,27,30,32,34,35,[38][39][40], while the other three showed a partial or complete mediating effect [8,33,37]. These findings were contradicted by other investigations published during the same period [28,31].…”
Section: Step 3: Theoretical Frameworkmentioning
confidence: 84%
“…Regarding the correlation between VL and vaccine acceptance, in two web surveys [34,35], Maneesriwongul et al have explored Thai parental attitudes and VL about COVID-19 vaccination. While nearly all parents of children under five years of age received their own vaccine, only 45% intended on vaccinating their child.…”
Section: Findings From the Review Updatementioning
confidence: 99%
“…Moreover, previous studies in Egypt [ 57 ] and the Democratic Republic of the Congo [ 10 ] also found that healthcare workers’ attitudes toward COVID-19 vaccination were a main predictor of acceptance [ 10 , 57 ]. Additionally, attitudes toward COVID-19 vaccines were predictors of acceptance among people living in Thailand [ 27 ] and among Thai parents [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that VL is associated with gender, and as children are a priority group for vaccination, there may also be differences in the effect of parents’ VL on childhood vaccination or vaccine hesitancy, but most of the current studies have examined the effect of VL on vaccine hesitancy and vaccination using children’s parents as a whole, with less in-depth exploration of this gender difference. 27–29 , 82 Clusters 2 and 4 showed that it is possible to further explore whether and why there is a gender difference between mothers’ and fathers’ VL on childhood vaccination or vaccine hesitancy, in order to develop appropriate strategies to improve childhood vaccination.…”
Section: Discussionmentioning
confidence: 99%